2021
DOI: 10.1093/jalm/jfab054
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Urine Collection with a Novel External Catheter Device on Common Urine Chemistry and Urinalysis Results

Abstract: Introduction Urine collection from incontinent individuals can be challenging. Various methods have been devised to collect the sample without catheterization. Recently the PureWick external catheter was developed to draw the sample gently away from external female genitalia. While the primary purpose of the device is to prevent moisture and maintain skin integrity, the urine that is collected may be sent for laboratory analysis. We sought to validate the use of this collection method for com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Urine Specimen Collection 5 20,29,38,39,42 There were several reports of successful urine diversion and input/output measurements. Validation studies confirmed good agreement between urine samples from normal voiding and PureWick collection for several analytes, including urine protein concentrations.…”
Section: Feuwds Are Favored To Iucsmentioning
confidence: 99%
“…Urine Specimen Collection 5 20,29,38,39,42 There were several reports of successful urine diversion and input/output measurements. Validation studies confirmed good agreement between urine samples from normal voiding and PureWick collection for several analytes, including urine protein concentrations.…”
Section: Feuwds Are Favored To Iucsmentioning
confidence: 99%